The classical approximative methods in game theory - Vilkas, E.; Sūdžiūtė, D. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. И. Вилкас, Д. Г. Суджюте. Классические приближенные методы в теории игр E. Vilkas, D. Sūdžiūtė, Klasikiniai apytiksliai metodai lošimų teorijoje